The Effect of Garlic Extract Addition on The Cholesterol Content of Male Castrated Crossbred Boer Meat - Imam Thohari; Susrini Idris; Balqis Yuniar (Faculty of Animal Science Universitas Brawijaya, 2007)
The objective of this research was to find out the effect of garlic extract addition on the content of male castrated Crossbred Boer meat cholesterol. Materials of this research were loin (Latissimus dorsi), leg (Bicep femoris), and shoulder (Triceps) of four male castrated Crossbred Boer goats. The meat part was ground together and 25 gram was taken for sample preparation. The garlic extract levels were 0% (E0), 1% (E1), 2% (E2), and 3% (E3). The results showed that garlic extract did not give a significant effect on the total cholesterol, LDL, and HDL of Crossbred Boer meat. It seemed that garlic extract could decrease the cholesterol and phospholipids content of the blood but the use of extract up to 2% could not decrease the cholesterol in meat significantly. However, the use of 3% garlic extract showed an unpredictable result i.e.: the chromatograms did not show any cholesterol content in meat. It was recommended to conduct a further research by applying garlic extract between 2% up to 3%. Â Keywords: cholesterol, garlic extract, male castrated Crossbred Boer meat